Issues and Challenges in Digitalizing Local Content: An analysis of Three Academic Libraries in Ogun State, Nigeria - Ozonuwe, Opene Sunday; Aluko, Oluwakemisola Omobolanle; Ogunojemite, Abosede Tola; Olaseigbe , Yetunde Faith; Rotimi , Racheal Ajibola; Giwa, Ayomide Ayoola; Giwa , Ayokunle Oluwadamilola (International Journal of Knowledge Content Development & Technology, 2026)
This study examines the issues and challenges associated with the digitalisation of local content in three academic libraries in Ogun State, Nigeria: Federal University of Agriculture Library (Nimbe Adedipe Library), Olabisi Onabanjo University Library, and Covenant University Library (Centre for Learning Resources). The objectives include assessing the extent of digitalisation, identifying types of local content digitised, understanding librarians’ attitudes towards digitalisation initiatives, exploring reasons for digitalisation, identifying challenges encountered, and proposing strategies to overcome these challenges. A survey research design was adopted, covering a population of 84 personnel, including librarians, library officers, and system analysts. Data were collected using structured questionnaires and phone interviews. The Statistical Package for Social Sciences (SPSS) version 23 was employed for data analysis, with results presented using frequency tables, percentages, and charts. Findings indicate that the extent of digitalisation in the studied academic libraries is moderately high, with faculty expertise directories, theses, and dissertations having the highest digitalisation rates. Librarians’ attitudes toward digitalisation were both positive and negative, with many recognizing its benefits for skill development, research, and institutional visibility, while concerns about copyright abuse, resistance to change, and technological adaptation persisted. The primary motivations for digitalisation included increased accessibility, cost-effectiveness, and cultural heritage preservation. Challenges identified included copyright and ownership issues, data privacy concerns, limited infrastructure, high equipment costs, insufficient funding, and a lack of skilled personnel. The study concluded that while digitalisation efforts are progressing in academic libraries, significant challenges hinder full implementation. The study recommended strategies for overcoming these challenges include adopting emerging technologies, enhancing digital infrastructure, addressing legal and copyright issues, capacity building, increasing awareness and support, and promoting open-access initiatives.